Armando's island - Arnold, Marsha Diane 1948- (Creative Editions, 2023)
"Armando's home is the rainforest-he knows its sights, smells, tastes, and sounds. He even knows its moods. From the bottom of the forest floor to the top of the emergent layer, the trees are also home to a multitude of creatures. When outsiders begin laying claim to and destroying the surrounding landscape, the displaced animals find refuge with Armando in the only remaining pocket of untouched forest, his "island." As people come in and animals are forced out, this poignant tale shows the cumulative and disastrous effects of Amazon deforestation."--
Keywords: Waldökosystem; Entwaldung; Auswirkung; Indigenes Volk; Umweltschaden; Waldtiere; Regenwald; Amazonas-Gebiet; Deforestation / Amazon River Region / Juvenile literature; Rain forest animals / Habitat / Conservation / Amazon River Region / Juvenile literature; Rain forest ecology / Amazon River Region / Juvenile literature; NATURE / Ecosystems & Habitats / Forests & Rainforests; Amazon River Region; Bilderbuch